Faktor – Faktor Yang Berhubungan Dengan Kejadian Pneumonia Pada Balita Di RSUD Lewoleba - Iser Leonardus; Lina Dewi Anggraeni (Poltekkes Kemenkes Surakarta, 2019)
Background: Pneumonia is an inflammation occurs in the lung parenchymal tissue. Profil Kesehatan Provinsi Nusa Tenggara Timur at 2015 show the scope of the discovery and the handling of pneumonia in toddlers at 3.757 (reached 6.03 %) and based on district, kabupaten lembata was ranked to 4 with 12 % of cases. The purpose of this research is to know about determine of factors that associated with the incidence of pneumonia in children under-five years old at the Lewoleba hospital. Method: quantitative method with descriptive correlative research design and cross sectional approach, sample in research 65 with totality sampling. Result: showed that correlation between parent education level (p value = 0,000), nutritional status of children under five years old (p value = 0,000), history of low birth weight (p value = 0,000), presence of family member of smokers (p value = 0,000), use of cooking fuel (p value = 0,000), and knowledge of parents (p value = 0,000) with pneumonia incidence in under-five children. Conclusion: Health workers expected can give health promotion such as prevention to parental of children under-five years old.